Differential expression and correlation analysis of global transcriptome for obstructive sleep apnea hypopnea syndrome - Chen, Ziyi; Wang, Guihua; Song, Lichen; Zhang, Yuanyuan; Wang, Guangming (Frontiers in Molecular Biosciences, 2025)
In order to investigate the gene expression patterns and molecular regulatory mechanisms of obstructive sleep apnea hypopnea syndrome (OSAHS), the global transcriptome expression profiles of OSAHS patients and healthy people were analyzed using transcriptome sequencing technology. Differential expression of circular RNA, microRNA, long noncoding RNA, and messenger RNA was investigated between the two groups. To further explore the role of differentially expressed genes in OSAHS, we functionally annotated the differentially expressed genes using enrichment analysis of GO and KEGG pathways. Finally, the ceRNA regulatory network of OSAHS was constructed. And validate the differentially expressed mRNA through qRT-PCR analysis. The results showed that 349 circRNAs,552 lncRNAs,205 miRNAs, 502 mRNAs were differentially expressed in patients with OSAHS compared with the healthy population. Terms such as centrosome, positive regulation of execution phase of apoptosis, oxidoreductase activity, regulation of Th 17 cell differentiation and immune response, neutrophil mediated cytotoxicity were enriched in the GO list, suggesting a potential correlation with OSAHS. Pathway analysis showed that Ferroptosis, Herpes simplex virus 1 infection, Pathways in cancer, Hematopoietic cell lineage and other pathways play an important role in OSAHS. By constructing a ternary network, two circRNAs and four lncRNAs were screened as ceRNAs to compete with miRNAs in the co-expression network, and associated with OSAHS by regulating the function of mRNAs in the network. By constructing a quaternary network miR-8485 and miR-6089 were found to be the top two ranked miRNAs most closely associated with OSAHS. Both qRT-PCR and transcriptome sequencing analysis showed similar trends. This provides more theoretical basis for exploring the complex molecular mechanisms of global transcriptome in the development of OSAHS.